Humayun Kabir, Men and Rivers, and Faridpur - Hasan, Md. Mahmudul (2022)
In the history of South Asian literature in English, Men and Rivers is the third fictional work written by a Muslim author after Rokeya's Sultana's Dream and Ahmed Ali's Twilight in Delhi (1940). Men and Rivers is a literary work of great merit though more research needs to be conducted on the work to appreciate its value by examining various thematic and stylistic features. Through Men and Rivers, Hamayun Kabir conferred on Faridpur literary immortality. I believe the novel will continue to make the district memorable and special to its readers for a very long time.